Optimizing the Digital Learning Experience: A Behavioral Model of Distance Student Engagement with the Learning Management System - Alam, Ghasa Faraasyatul; Imron, Ali; Arifin, Imron; Juharyanto, Juharyanto; Subairi, Muhammad Zulhairi Bin (Pascasarjana UM, 2023)
This study investigates the influence of students' intentions to utilize and engage with remote learning management systems (LMS) on the enhancement of educational quality. Through a comprehensive literature review, this research synthesizes existing findings to understand the interplay between student engagement with LMS in remote learning contexts and its effects on the quality of education in higher education institutions. The analysis demonstrates that students' behavioral intentions toward adopting LMS are crucial in improving educational outcomes. Significant insights from this study highlight the LMS as: (a) an essential tool for accessing educational content, (b) a robust platform for facilitating effective distance learning, and (c) a key element in advancing the quality of learning experiences in higher education. By examining the existing literature, this research underscores the importance of digital engagement in the educational landscape, offering valuable implications for educators, policymakers, and institutions aiming to enhance learning through technology.